Fish trade in Norse Orkney and Caithness : a zooarchaeological approach - Barrett, James H.
The trade of dried fish played an important role in the transformation from the Viking Age to the Middle Ages in Scandinavian polities such as Arctic Norway. This paper develops zooarchaeological methods to investigate whether similar processes occurred in the less well documented Norse colonies of northern Scotland Ñ the joint earldoms of Orkney and Caithness.